CHINA'S ENERGY DIPLOMACY TOWARDS RUSSIA IN THE EASTERN SIBERIA PIPELINE DEVELOPMENT DURING PRESIDENT XI JINPING PERIOD - Muhamad Firmansyah; Silvia Dian Anggraeni (Universitas Jenderal Ahmad Yani, 2021)
China is a very active country in building energy diplomacy relations towards Russia. Since the end of the Cold War, the intensity of energy relations between the two countries has been increasing, one of which is related to the Eastern Siberian pipeline project. The Eastern Siberian pipeline project is a strategic project for China to maintain the stability of their energy security in the future. This is what makes China under the leadership of Xi Jinping, increasingly seeking to improve their energy diplomacy relations towards Russia in an effort to develop the Eastern Siberian pipeline project which includes two major projects, specifically oil pipeline through the Eastern Siberian Pasific Ocean (ESPO) and the natural gas pipeline through the Power of Siberia. Using qualitative research methods and literature reviews, the authors sought to provide an in-depth analysis of China's implementation of energy diplomacy against Russia in the development of the Eastern Siberian pipeline. China's energy diplomacy towards Russia is part of efforts to diversify China's energy imports many involving actors of China's national energy companies. This research also proves that energy cooperation relationships are not only built within bilateral frameworks but also in multilateral frameworks as part of China-Russia efforts to accelerate the development of the Eastern Siberian pipeline.